Ideology and identity: ‘knowing’ workers in early Soviet Russia, 1917-1921 - Sumner, Laura Marie (2018)
The period 1917-1921 provides an insight not only into the policies of the new Soviet state but the mindset of its leaders. These four years were a time of intense political struggle and socio-economic disruption, which exposed the tension between ideology and practice in Bolshevik discourse and policy making. Workers, specifically metalworkers, were a focal point of Bolshevik ideology and policies in this period. This thesis will explore how the Soviet state conceptualised metalworkers, through ideology, and how this informed their engagement with workers, through policy. This will be done through an examination of state statistical data and how prominent state polices, cultural policy and treatment of dissent, and discourse changed over this period. It will also focus on a case study of Sormovo Metalworks, a suburb of Nizhnii Novgrorod, and use local sources to investigate how the tension between ideology and practice played out on a local level. It will explore how local Bolsheviks conceptualised and engaged with Sormovo workers and how this was shaped by three things: Bolshevik ideology, the context of the Civil War and the specific local conditions of Sormovo and its workforce. The Civil War period witnessed a change in the discourse and policies of the Soviet state, which became more coercive, interventionist and repressive as the war progressed. Sormovo Metalworks was a large metalworking complex in a largely rural province; it had a skilled workforce with a tradition of labour activism through striking and was dominated by the Socialist Revolutionary Party. The move towards an increasingly centralised state was utilised by local Bolsheviks in Sormovo in an attempt to end the labour activism of its workforce and crush political opposition. However, despite the increasingly assertive discourse about the identity of metalworkers and the state’s drive for economic, political and cultural centralisation, Sormovo workers had the ability to challenge, subvert and negotiate state labels and even policies. This case study reveals that although Sormovo workers suffered repeated challenges to their identity by the state, local government and the economic crises of the Civil War, they continued to utilise self-identification based on their skill and shared socio-economic experience. This in turn shaped their vertical and horizontal social, economic and political relationships with those around them. Although the central state became politically and economically centralised and authoritarian, the identity of the grassroots in Sormovo remained diverse and fluid.